2005
DOI: 10.1097/00001756-200508010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroids protect retinal pigment epithelium against oxidative stress

Abstract: This study was undertaken to assess whether neuroactive steroids, 17β-estradiol and dehydroepiandrosterone-sulfate, enhance survival and protect DNA of human retinal pigment epithelial cells challenged by oxidative stress, and to investigate the role of σ 1 receptors in the effects of neuroactive steroids. Retinal pigment epithelial cells were treated with various concentrations of neuroactive steroids and then exposed to hydrogen peroxide. Pretreatment with steroids resulted in significant increased viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…In ARPE-19 cells, other time points and other toxicity measures have been used [916,35,4648]. Although H 2 O 2 concentration changes dynamically over time especially after pulse addition, outcomes are typically determined at a fixed post-treatment interval.…”
Section: Resultsmentioning
confidence: 99%
“…In ARPE-19 cells, other time points and other toxicity measures have been used [916,35,4648]. Although H 2 O 2 concentration changes dynamically over time especially after pulse addition, outcomes are typically determined at a fixed post-treatment interval.…”
Section: Resultsmentioning
confidence: 99%
“…Since the physiological function of RPE cells is responsible for clearance of oxidants derived from photoreceptor turnover, ARPE-19 cells have been used to explore oxidant-mediated insults and related protective factors in a number of recent studies. Hepatocyte growth factor (HGF), pigment epithelium-derived factor, keratinocyte growth factor, sigma receptor ligands and neuroactive steroids have been shown to prevent oxidantinduced apoptosis in ARPE-19 cells [7,29,[37][38][39]. In these studies, pretreatment with HGF abrogated oxidant-mediated AIF translocation; however, the underlying mechanism has not been elucidated [7].…”
Section: Discussionmentioning
confidence: 99%
“…24 NS are also involved in the antioxidant defense mechanisms of the nervous system. 25,26 The results of an earlier study has shown that PROG inhibits the lipid peroxidation as evidenced by the reduced levels of 8-isoprostaglandin F2 alpha in brains of PROGtreated rats in a cerebral contusion model. 27 In another study, DHEA pretreatment was found to reduce DNA damage induced by oxidative insult.…”
Section: Introductionmentioning
confidence: 99%